2004
DOI: 10.1289/ehp.6564
|View full text |Cite
|
Sign up to set email alerts
|

Phthalate exposure and pulmonary function.

Abstract: Exposure to phthalates is widespread because of their use in plastics, cosmetics, and other consumer products. Phthalate exposure has been associated with adverse respiratory outcomes in children. With urinary phthalate measures, we assessed the association between phthalate exposure and four pulmonary function parameters [forced vital capacity (FVC), forced expiratory volume at 1 sec (FEV1), peak expiratory flow (PEF), and maximum mid-expiratory flow] among the 240 adult Third National Health and Nutrition Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
7
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(93 citation statements)
references
References 19 publications
2
81
7
3
Order By: Relevance
“…These findings have not been replicated, but several authors have suggested that PVC medical tubing may be a likely source of respiratory health effects in young neonates (Hill et al 2001(Hill et al , 2003Tickner et al 2001). One study of adults found an inverse relationship between urinary MEP and MBP and pulmonary function (Hoppin et al 2004), but because urine markers reflect all routes of exposure and may not be a good measure of inhaled phthalate concentrations, it is difficult to interpret these results. Given these findings, further research needs to examine route-or target-specific phthalate biomarkers of exposure and potential pathophysiologic changes relating to the development of allergic and asthmatic diseases and pulmonary function in children.…”
Section: Phthalates (A) Exposurementioning
confidence: 99%
“…These findings have not been replicated, but several authors have suggested that PVC medical tubing may be a likely source of respiratory health effects in young neonates (Hill et al 2001(Hill et al , 2003Tickner et al 2001). One study of adults found an inverse relationship between urinary MEP and MBP and pulmonary function (Hoppin et al 2004), but because urine markers reflect all routes of exposure and may not be a good measure of inhaled phthalate concentrations, it is difficult to interpret these results. Given these findings, further research needs to examine route-or target-specific phthalate biomarkers of exposure and potential pathophysiologic changes relating to the development of allergic and asthmatic diseases and pulmonary function in children.…”
Section: Phthalates (A) Exposurementioning
confidence: 99%
“…Diethylhexyl phthalate and dibutyl phthalate have hepatic and renal effects at high doses and cause hepatocellular carcinoma, anovulation, and decreased fetal growth (Hauser and Calafat, 2005). There are also some effects in relation to phthalate exposure on respiratory function, metabolism, and thyroid function of humans (Hoppin et al 2004;Stahlhut et al 2007;Meeker et al 2007). …”
Section: Effect Of Phthalic Acid Esters On Human Healthmentioning
confidence: 99%
“…Sources of phthalate exposure include the workplace, diet, off-the-job activities, personal care products, and other home or environmental sources. Phthalates have been evaluated as possible reproductive and developmental toxicants in animals and humans (Hauser and Calafat, 2005;Latini, 2005;Heudorf et al, 2007;Matsumoto et al, 2008) and may also have a function in respiratory disease (Bornehag et al, 2004;Hoppin et al, 2004;Jaakkola and Knight, 2008;Kolarik et al, 2008).…”
Section: Introductionmentioning
confidence: 99%